Qiyas Sebagai Salah Satu Metode Istinbāṭ Al-Ḥukm (UINSI Samarinda, 2016)
One of the methods of deriving Islamic law which is widely known in the study of usul fiqh is qiyas. Qiyas is very popular among the scholars of Shafi’i. In simple terms, qiyas can be interpreted as an attempt to equate the law of a case that does not have a legal naṣṣ to the case that already has a legal naṣṣ, because of the equation of 'illat. This article try to study qiyas as one method in istinbāṭ al-ḥukm by describing several aspects including the elements, requirements and steps that must be passed by a mujtahid who want to derive Islamic law through qiyas method.